2009
DOI: 10.1111/j.1749-6632.2009.03843.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin Promotes Clustering, Migration, and Activation States of Mononuclear Myelocytic Cells

Abstract: Monocytes are leukocytic precursors of macrophages, dendritic cells, and osteoclasts, with critical roles in inflammation and tumor biology. Tumors can elicit signals that activate monocytes to extravasate, infiltrate tumors, and differentiate into tumor-associated macrophages (TAMs), which can modulate host immune surveillance. In order to assess whether relaxin can influence monocyte activation status, we assessed its ability to alter cell-cell clustering and cytokine expression of the monocytic cell line TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Consistent with previous studies, relaxin can promote the acquisition of an immunosuppressive M2 phenotype in macrophages; M2 macrophages suppress kidney inflammation by releasing anti-inflammatory mediators, such as IL-10, thus inhibiting renal fibrosis [3, 4, 5, 10]. We also found that relaxin can downregulate the TLR4-NF-ΚB signaling pathway at all levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with previous studies, relaxin can promote the acquisition of an immunosuppressive M2 phenotype in macrophages; M2 macrophages suppress kidney inflammation by releasing anti-inflammatory mediators, such as IL-10, thus inhibiting renal fibrosis [3, 4, 5, 10]. We also found that relaxin can downregulate the TLR4-NF-ΚB signaling pathway at all levels.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our result, recent studies have shown that relaxin has the potential to shift macrophage polarization toward the M2 phenotype. Figueiredo et al found that in response to inflammatory stimuli, relaxin can suppress expression of the typical M1-cytokine IL-1β in macrophages, thus promoting acquisition of an immunosuppressive M2 phenotype in macrophages [10]. Binder et al investigated the mechanism of relaxin-enhanced breast tumor growth and found that tumor growth was enhanced because relaxin can switch macrophages toward the M2 phenotype [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally, RXFP1 was less frequently expressed in control tumours than in tumours from relaxin-treated mice ( p  < 0.01). Since macrophages are responsive to relaxin [21], we measured the amount of TAM in the various tumour samples. In fact, there was a significantly higher degree of TAM infiltration in the relaxin-exposed tumours than in the controls.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that not only the TAM, infiltrating from the peripheral blood, but also resident macrophages at the site of metastasis are critical for the colonization of distant organs [19, 20]. Interestingly, Figueiredo et al [21] have shown that relaxin inhibits expression of the typical M1-cytokine IL 1β in rat macrophages, thus indicating a potential role for relaxins in the tumour-associated phenotype shift to M2.…”
Section: Introductionmentioning
confidence: 99%